Sex Differences in Autonomic Blood Pressure Regulation: Sex Chromosome Complement and Hormonal Involvement - Caeiro, Ximena Elizabeth (2023)
Although several lines of evidence from different studies highlight sex differences in cardiovascular diseases, to date, most studies have been focused on males, with the idea that males and females are similar, differing only in the magnitude of the response. However, the principles learned in male models cannot and should not be extrapolated to women and, therefore, it is important to study in greater detail not only the differences between the sexes but also the physiological intertwining of the underlying genetic and hormonal mechanisms of sexual dimorphism. This review explores the sex disparities in the autonomic nervous system regulation of blood pressure (particularly baroreceptor function), with special emphasis on sex hormones and sex chromosome complement factors involved in sexually dimorphic autonomic blood pressure regulation. A more detailed understanding of the sources of physiological disparities between the sexes may also help in understanding the differences between the sexes in rates of cardiovascular disease and may also aid in designing future improvements for sex-tailored therapeutic treatments.